2013
DOI: 10.1002/wcs.1216
|View full text |Cite
|
Sign up to set email alerts
|

Emotion and moral judgment

Abstract: Research in psychology and cognitive science has consistently demonstrated the importance of emotion in a wide range of everyday judgments, including moral judgment. Most current accounts of moral judgment hold that emotion plays an important role, but the nature and extent of this role are still debated. We outline three increasingly strong claims about the role of emotion in moral judgment and assess the evidence for each. According to the first and least controversial claim, emotions follow from moral judgm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(55 citation statements)
references
References 74 publications
4
50
0
1
Order By: Relevance
“…There is plenty of evidence to support the claim that emotions motivate individuals to reject harmful transgressions 23,115 , even if such actions are necessary to stave off harm of bigger magnitude 49 . Recent research also sheds light on the exact nature of psychological processes that constitute this negative affect 75,115 : aversion to harmful outcome (e.g.…”
Section: Dissociable Empathy-utilitarianism Associations Between Autimentioning
confidence: 99%
See 1 more Smart Citation
“…There is plenty of evidence to support the claim that emotions motivate individuals to reject harmful transgressions 23,115 , even if such actions are necessary to stave off harm of bigger magnitude 49 . Recent research also sheds light on the exact nature of psychological processes that constitute this negative affect 75,115 : aversion to harmful outcome (e.g.…”
Section: Dissociable Empathy-utilitarianism Associations Between Autimentioning
confidence: 99%
“…Emotions play a pivotal role in condemnation of harmful behaviours 23 and empathy is a social emotion that plays a crucial role in such moral evaluations 24,25 . This is because (real or hypothetical) harmful encounters include a suffering victim and empathy allows moral judges to understand their suffering and use the resulting "gut-feelings" to either approve or disapprove of such moral actions 25 .…”
mentioning
confidence: 99%
“…Pelzer (2005) noted in a review that contempt seems to be very much present in organizational practice yet ignored by research. But interest in contempt appears to be growing, and researchers have approached the topic from the angle of hostility in social interactions (Fischer & Roseman, 2007), as a moral emotion (Haidt, 2003;Hutcherson & Gross, 2011;Mason, 2003;Rozin, Lowery, Imada, & Haidt, 1999), as an amplifier in moral judgments (Avramova & Inbar, 2013;Horberg, Oveis, & Keltner, 2011;Laham, Chopra, Lalljee, & Parkinson, 2010), and as an influence in emergent leadership categorization (Melwani, Mueller, & Overbeck, 2012). The majority of contempt research has been carried out within psychology, where contempt is often envisioned as a basic emotion, indeed going back to the work of Charles Darwin who viewed contempt as a universal, primary emotion shared by all societies (Pelzer, 2005).…”
Section: Contemptmentioning
confidence: 99%
“…The only studies that provided additional evidence on this are Schnall et al (2008); whose findings suggested that disgust did not influence non-moral judgments (i.e., not rendering them more severe), and, Wheatley and Haidt (2005), who did suggest that disgust renders non-moral behaviors as judged more severely. Although, there have undoubtedly been other studies not included here (e.g., Nichols, 2002) that have suggested that disgust also exerts a moralizing function (i.e., morally neutral behaviors that can be given a moral status just because they perceived as being disgusting), the empirical evidence is too limited to draw a clear-cut conclusion (see Avramova & Inbar, 2013;Pizarro, Inbar, & Helion, 2011 for a review). Furthermore, regarding disgust as a trait, there are generally no studies that examined the possibility of whether disgust sensitivity could also be associated with evaluations of non-moral contexts.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%